Physiotherapists' ethical behavior in professional practice: a qualitative study - Marmol-Lopez MI; Marques-Sule E; Naamanka K; Arnal-Gomez A; Cortes-Amador S; Durante A; Tejada-Garrido CI; Navas-Echazarreta N; Juarez-Vela R; Gea V (FRONTIERS MEDIA SA, 2025)
Background: In health professions, ethics is considered a fundamental competence. The increase in clinical autonomy in the field of physiotherapy is associated with an increase in ethical situations in their clinical practice.
Objective: To explore the ethics of the clinical relationship between physiotherapists and patients, the ethics training received by physiotherapists, and if in the clinical context, physiotherapists identify the necessary attitudes and apply the ethical recommendations of the profession for the ethical situations they experience.
Methods: A qualitative exploratory and descriptive study was performed with physiotherapists. Data were collected through semi-structured interviews. The data were analyzed using content analysis, as proposed by Krippendorf. The study protocol was approved by the University of Valencia Ethics Committee of Human Research.
Results: This study included 15 physiotherapists (66.66% women, average age = 42.2 years), which was sufficient to reach data saturation. We identified four categories: (i) Ethics of the clinical relationship (ethical values, principles, and norms; type of clinical relationship), (ii) Ethics training received (during the physiotherapy studies; current training of students; low importance of ethics in the curriculum), (iii) Necessary attitudes for professional ethical practice (main attitudes were identified: personal attitudes and professional attitudes); (iv) Experiences from professional practice (general; public sector vs. private sector).
Conclusion: The ethics of the clinical relationship between physiotherapists and patients is determined by the attitudes of the practitioner, which are the result of his or her values and previous experiences; and are very centered on ethics of indication (founded mainly on the principles of Beneficence and Non-Maleficence). It is necessary to improve the ethical training received by physiotherapists, which is poorly focused on professional attitudes.